Imaging of Mitochondrial and Cytosolic Ca2+ Signals in Cultured Astrocytes. Issue 1 (22nd January 2018) - Zhang, Nannan; Ding, Shinghua
Abstract: This unit provides a step‐by‐step protocol for constructing cell type‐ and mitochondria‐targeted GCaMP genetically encoded Ca 2+ indicators (GECIs) for mitochondrial Ca 2+ imaging in astrocytes. Mitochondrial Ca 2+ plays a critical role in controlling cytosolic Ca 2+ buffering, energy metabolism, and cellular signal transduction. Mitochondrial Ca 2+ overload contributes to various pathological conditions, including neurodegeneration and apoptotic cell death in neurological diseases. Live‐cell mitochondrial Ca 2+ imaging is an important approach to understand mitochondrial Ca 2+ dynamics and thus cell physiology and pathology. We implement astrocyte‐specific mitochondrial targeting of GCaMP5G/6s (mito‐GCaMP5G/6s). By loading X‐Rhod‐1 into astrocytes, we can simultaneously image mitochondrial and cytosolic Ca 2+ signals. This protocol provides a novel approach to image mitochondrial Ca 2+ dynamics as well as Ca 2+ interplay between the endoplasmic reticulum and mitochondria. © 2018 by John Wiley & Sons, Inc.